PENGGUNAAN MATERIAL BEKAS PELUANG MENUJU SUSTAINABLE DESIGN - Oc. Cahyono Priyanto (Ars: Jurnal Seni Rupa dan Desain, 2008)
environmental damages are acknowledged to be the negative impacts of the existence and activities of human. The impacts have been the major issues in the world such as the ozone hole, the earth temperature that is increasing significantly and the natural disasters. People need to change their paradigms and habits immediately to prevent further destruction on earth. Reutilizing used materials is one way, among other ways, to lessen the environment exploitation, even though it is not directly related to carbon dioxide reduction issue which is promoted by the KyotoProtocol supporters. However, in the realm of art and design, it is really relevant to creativity and at the same time, endorsing the sustainable design principles. Keywords: sustainable design, recycle, reused material